2006
DOI: 10.1016/s0022-5347(06)00563-5
|View full text |Cite
|
Sign up to set email alerts
|

Localization of M 2 and M 3 Muscarinic Receptors in Human Bladder Disorders and Their Clinical Correlations

Abstract: To our knowledge this is the first study to show the cellular localization of muscarinic receptor subtypes 2 and 3 in the human bladder. The increase in muscarinic receptor subtypes 2 and 3 immunostaining in myofibroblast-like cells in clinical bladder syndromes and its correlation with clinical scores suggests a potential role in pathophysiological mechanisms and the therapeutic effect of anti-muscarinic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
1
11

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(133 citation statements)
references
References 17 publications
4
117
1
11
Order By: Relevance
“…It has been reported that nicotinic and muscarinic cholinergic receptors are widely expressed on non-neuronal cells including intestinal, skin and urinary bladder epithelial cells, immune cells as well as myofibroblasts Hegde, 2006;Beckel et al, 2005;Mukerji et al, 2006). In the present study, 3 H-ACh evoked release was unmasked by atropine suggesting this was mediated by activation of nicotinic receptors.…”
Section: Discussionsupporting
confidence: 56%
“…It has been reported that nicotinic and muscarinic cholinergic receptors are widely expressed on non-neuronal cells including intestinal, skin and urinary bladder epithelial cells, immune cells as well as myofibroblasts Hegde, 2006;Beckel et al, 2005;Mukerji et al, 2006). In the present study, 3 H-ACh evoked release was unmasked by atropine suggesting this was mediated by activation of nicotinic receptors.…”
Section: Discussionsupporting
confidence: 56%
“…A recent report (31) also demonstrated a high density of M 2 muscarinic receptors in the human bladder mucosa. Furthermore, Mukerji et al (32) reported that M 2 -and M 3 -immunoreactive staining was present in human detrusor, myofibroblast-like cells, nerve fiber bundle, and dorsal root ganglion of small and medium sensory neurons in suburothelium. These muscarinic receptors might be targets of non-neuronal ACh from urothelium.…”
Section: +mentioning
confidence: 99%
“…An increased density of M2 protein and a decrease of M3 protein have been reported in decentralised 14 , obstructed 15 , and neurogenic 17 rat bladders. Also, there is evidence that expression of M2 and M3 mAChR subtypes are altered on the urothelium and suburothelial interstitial cells 29 in different bladder pathologies. These changes may account for the increased sensitivity for mAChR agonists in SCI rats.…”
Section: Discussionmentioning
confidence: 99%